A study on the influence of substrate pre-heating on mitigation of cracks in direct metal laser deposition of NiCrSiBC-60%WC ceramic coating on Inconel 718 - Sadhu, Abhijit; Choudhary, Amit; Sarkar, Sagar; Nair, Amal M.; Nayak, Pravanjan; Pawar, Sagar Dadasahed; Muvvala, Gopinath; Pal, Surjya K.; Nath, Ashish Kumar (Surface & coatings technology, 2020)
Direct metal laser deposition of ceramic-metal composite coatings has received much attention in the recent past over other conventional methods due to a large number of advantages. However, formation of cracks due to large thermal gradients and rapid cooling rates limits its application. Therefore, in the present study the influence of cooling rate on crack mitigation in multilayer direct metal laser deposition of NiCrSiBC-60%WC on Inconel 718 substrate has been investigated by monitoring the thermal history of the molten pool using an IR pyrometer. Cracks could not be mitigated by varying the cooling rate through changing the scan speed within the present experimental range of 300 mm/min to 700 mm/min, possibly due to the large thermal gradients build up between the substrate and the deposited clad track. Therefore, in order to decrease the cooling rate and the thermal gradient, and study their effect on crack mitigation pre-heating of the substrates at two different temperatures, 300 °C and 500 °C was employed during the deposition process. Crack-free coatings could be obtained with substrate pre-heating, except at the lower pre-heating temperature of 300 °C and the highest scan speed of 700 mm/min which had yielded a relatively fast cooling rate. Also, at the higher pre-heating temperature of 500 °C and the lowest scan speed of 300 mm/min scan speed micro-cracks were observed inside the coating due to severe dissolution of WC particles making the matrix brittle. Further, residual stresses, hardness and wear resistance of the deposited coating under above experimental conditions were determined and correlated with the cooling rate and the microstructure. •Laser cladding of NiCrSiBC–60%WC on Inconel 718 is carried out and the molten pool thermal history is monitored.•Effect of scan speed, substrate pre-heating and corresponding cooling rates on mitigation of cracks is investigated.•Influence of cooling rate on WC decomposition and resulting hardness and wear characteristics is investigated.